Photo-oxidative degradation of toluene in aqueous media by hydroxyl radicals - Hatipoglu, Arzu; Vione, Davide; Yalcin, Yelda; Minero, Claudio; Cinar, Zekiye (ELSEVIER SCIENCE SA, 2010)
This study has the goal of determining the most probable reaction path and the product distribution for the photo-oxidative degradation of toluene in aqueous media. A combination of experimental and quantum mechanical methods were used to elucidate the effect of water solvent on the reaction rate and on the subsequent formation of the primary intermediates. In the experimental part of the study, the formation yields of hydroxylated intermediates and of benzaldehyde were measured by HPLC, in the presence of nitrate under UVB irradiation as the (OH)-O-center dot source. Modeling of the reaction paths was performed with density functional theory (DFT) calculations, to investigate the most plausible mechanism for the initial (OH)-O-center dot attack and to determine the identities of the primary intermediates. Rate coefficients for all the reaction paths were computed by the Transition State Theory (TST) to obtain the product distribution. The effect of solvent water was investigated by using COSMO as the solvation model. The experimental results combined with DFT calculations indicate that ortho-addition to finally give o-cresol is the dominant reaction path for gas and aqueous media. The presence of a dielectric medium such as water has a stabilizing effect that decreases the overall energy for this mechanism. Finally, the significance for surface waters of the reaction between toluene and (OH)-O-center dot was studied by use of a recently developed photochemical model that foresees the lifetime of a compound upon reaction with (OH)-O-center dot, as a function of the reaction rate constant, the chemical composition of the surface water layer, and the water column depth. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Toluene; Hydroxyl radical; Photo-oxidative degradation; DFT calculation; COSMO; MOLECULAR-ENERGIES; ORGANIC-COMPOUNDS; OH RADICALS; BENZENE; OXIDATION; VOLATILE; ADDUCTS; NITRITE; NITRATE; PHENOL; Chemistry